Role of Platelet-Derived Microvesicles As Crosstalk Mediators in Atherothrombosis and Future Pharmacology Targets: A Link between Inflammation, Atherosclerosis, and Thrombosis - Badimon, Lina; Suades, Rosa; Fuentes, Eduardo; Palomo, Iván; Padró, Teresa (Frontiers in Pharmacology, 2016)
Reports in the last decade have suggested that the role of platelets in atherosclerosis and its thrombotic complications may be mediated, in part, by local secretion of platelet-derived microvesicles (pMVs), small cell blebs released during the platelet activation process. MVs are the most abundant cell-derived microvesicle subtype in the circulation. High concentrations of circulating MVs have been reported in patients with atherosclerosis, acute vascular syndromes, and/or diabetes mellitus, suggesting a potential correlation between the quantity of microvesicles and the clinical severity of the atherosclerotic disease. pMVs are considered to be biomarkers of disease but new information indicates that pMVs are also involved in signaling functions. pMVs evoke or promote haemostatic and inflammatory responses, neovascularization, cell survival and apoptosis, processes involved in the pathophysiology of cardiovascular disease. This review is focused on the complex cross-talk between platelet-derived microvesicles, inflammatory cells and vascular elements and their relevance in the development of the atherosclerotic disease and its clinical outcomes, providing an updated state-of-the art of pMV involvement in atherothrombosis and pMV potential use as therapeutic agent influencing cardiovascular biomedicine in the future.